Histoire de l'URSS - Elleinstein, Jean; Hocquenghem, Guy; Laboureur, Sylvain; Mane, Roland; Roos, Nina; Thibault, Pierre (Paris : Larousse.)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Sovjet-Unie.